2023
DOI: 10.1111/nph.18682
|View full text |Cite
|
Sign up to set email alerts
|

Golovinomyces cichoracearum effector‐associated nuclear localization of RPW8.2 amplifies its expression to boost immunity in Arabidopsis

Abstract: Summary Arabidopsis RESISTANCE TO POWDERY MILDEW 8.2 (RPW8.2) is specifically induced by the powdery mildew (PM) fungus (Golovinomyces cichoracearum) in the infected epidermal cells to activate immunity. However, the mechanism of RPW8.2‐induction is not well understood. Here, we identify a G. cichoracearum effector that interacts with RPW8.2, named Gc‐RPW8.2 interacting protein 1 (GcR8IP1), by a yeast two‐hybrid screen of an Arabidopsis cDNA library. GcR8IP1 is physically associated with RPW8.2 with its REAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 66 publications
0
7
0
Order By: Relevance
“…Although the exact mechanisms governing the subcellular relocation of PbbZIP4 remain incompletely understood, this phenomenon may be influenced by the effectors produced by the pathogen. It has been demonstrated that the interaction between GcR8IP1 and RPW8.2 alters the cellular distribution of RPW8.2, increasing its localization in the nucleus (Zhao et al., 2023). This finding provides further support for the notion that interactions between proteins can affect the nucleocytoplasmic partitioning of transcription factors, potentially affecting their subcellular localization and functional activities.…”
Section: Resultsmentioning
confidence: 99%
“…Although the exact mechanisms governing the subcellular relocation of PbbZIP4 remain incompletely understood, this phenomenon may be influenced by the effectors produced by the pathogen. It has been demonstrated that the interaction between GcR8IP1 and RPW8.2 alters the cellular distribution of RPW8.2, increasing its localization in the nucleus (Zhao et al., 2023). This finding provides further support for the notion that interactions between proteins can affect the nucleocytoplasmic partitioning of transcription factors, potentially affecting their subcellular localization and functional activities.…”
Section: Resultsmentioning
confidence: 99%
“…To perform the subcellular localization and transcriptional activation assays, we transferred plasmids into tumefaciens strain GV3101. NLS-RFP served as a nuclear marker, as previously described [50,51]. For the subcellular localization assay, we introduced A. tumefaciens strains carrying the expression plasmids, along with the NLS-RFP plasmid, into the abaxial air space of 2 to 4-week-old Nicotiana benthamiana leaves via in ltration.…”
Section: Subcellular Localization Analysis and Transcriptional Activa...mentioning
confidence: 99%
“…In Arabidopsis, PM induced the expression of WRKY and RPW genes simultaneously for balancing immunity and growth (Yang et al, 2023). Resistance to PM 8.2 (RPW8.2) interacted with PM protein GcR8IP1 and amplified its expression to boost immunity (Zhao et al, 2023), and RPW8.2 engaged EDS1‐dependent and SA signalling to trigger a positive response to PM in Arabidopsis (Xiao et al, 2001). Collectively, molecular regulations can contribute to PM resistance in plants.…”
Section: Introductionmentioning
confidence: 99%
“…In Kentucky bluegrass, differentially expressed genes in photosynthesis were enriched in highly the PM resistant variety and had a feedback effect on plant immune defence (Zhang et al, 2022). When encountering pathogens, the specificity of pathogen recognition is often determined by a pathogen avirulence (avr) gene and a corresponding plant resistance (R) gene (Zhao et al, 2023). In Kentucky bluegrass, two R genes ( PRM and RPS ) and the RBOH gene were significantly inhibited, while the HSP90 gene was induced after infection with B .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation